The natural environment. The development of an institutional protection framework - a permanent concern of the European Union - Andreea Stoican (Juridical Tribune, 2020)
The environmental policy is a relatively new field in the European Union, even at the level of the current year, 2019. Although initially it was based on the creation of general measures programs, within which certain specific measures were adopted, currently, the permanent existing global climate changes can no longer be ignored by national, European or global organizations and institutions. As such, in time, especially in the last decade, the European Union has been forced, by virtue of the principles governing the relationship between the EU law and that of the Member States, to find solutions to the serious problems caused especially by pollution, but also by a series of other climatic causes. Thus, the environmental policy of the European Union is based on a number of principles, including that of precaution, prevention, diminish of pollution from its source, as well as that of the polluter's liability. In this regard, the present paper aims to summarize the measures taken so far at the level of the European Union, as well as to identify additional protective measures that will also lead to the fulfillment of the European Union Sustainable Development Strategy.